2020
DOI: 10.1007/s10549-020-05755-7
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival results from the randomized phase 2 study of palbociclib in combination with letrozole versus letrozole alone for first-line treatment of ER+/HER2− advanced breast cancer (PALOMA-1, TRIO-18)

Abstract: Purpose Palbociclib is a cyclin-dependent kinase 4/6 (CDK4/6) inhibitor, approved in combination with endocrine therapy for the treatment of women and men with hormone receptor-positive, human epidermal growth factor receptor 2-negative advanced breast cancer (HR+/HER2− ABC). In the phase 2, open-label, PALOMA-1 trial, palbociclib plus letrozole significantly prolonged progression-free survival (PFS) versus letrozole alone (hazard ratio, 0.488; 95% CI 0.319-0.748; P = 0.0004; median PFS, 20.2 vs 10.2 months, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 23 publications
3
81
0
5
Order By: Relevance
“…Currently, most of the safety data pertaining to CDK4/6 inhibitors received concomitantly during endocrine-based therapy for HR+/HER2- advanced breast cancer in women represent an evaluation after a relatively short follow-up period. The longest safety follow-up of any CDK4/6 inhibitor in the breast cancer setting is five years for palbociclib plus letrozole in the PALOMA-1 study (December 30, 2016, data cutoff), reported in conjunction with overall survival (12). Although these data were used to assess cumulative incidence annually over five consecutive years to reveal no new safety concerns, as a single study, it included only 83 patients, and, although informative, it must be viewed in that context.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most of the safety data pertaining to CDK4/6 inhibitors received concomitantly during endocrine-based therapy for HR+/HER2- advanced breast cancer in women represent an evaluation after a relatively short follow-up period. The longest safety follow-up of any CDK4/6 inhibitor in the breast cancer setting is five years for palbociclib plus letrozole in the PALOMA-1 study (December 30, 2016, data cutoff), reported in conjunction with overall survival (12). Although these data were used to assess cumulative incidence annually over five consecutive years to reveal no new safety concerns, as a single study, it included only 83 patients, and, although informative, it must be viewed in that context.…”
Section: Discussionmentioning
confidence: 99%
“…Palbociclib (Ibrance, Pfizer, NY, NY, USA) is the first-in-class CDK4/6i receiving an accelerated approval from FDA in February 2015, in combination with letrozole as initial therapy for postmenopausal women HR-positive, HER2-negative advanced, or metastatic BC, based on the results from the phase II trial PALOMA-1/TRIO-18, which showed a significant benefit in terms of progression-free survival (PFS) for combination therapy with palbociclib and letrozole over letrozole alone (median PFS 20.2 vs. 10.2 months, hazard ratio (HR) 0.49, p = 0.0004) [47]. Nevertheless, the trial cannot show a similar statistically significant increase of overall survival (OS), showing a median OS of 37.5 months in the palbociclib-letrozole group, as compared with 34.5 months in the placebo-letrozole group (HR 0.897, p = 0.281) [48]. These results were validated by conducting the phase III PALOMA-2 trial, which showed a final PFS of 27.6 months in palbociclib plus letrozolo arm, compared with 14.5 months in letrozole arm (HR 0.563, p < 0.001) and a clinical benefit rate (CBR) improved from 70.3% to 84.9% (p < 0.001) favoring palbociclib [49,50].…”
Section: Efficacy and Safety Profile Of Cdk4/6 Inhibitors In Hr-positmentioning
confidence: 99%
“…В первом же рандомизированном исследовании II фазы PALOMA-1 / TRIO-18 добавление палбоциклиба к летрозолу в 1-й линии терапии в 2 раза увеличило медиану ВБП, которая составила 20,2 мес для комбинации и 10,2 мес для одного летрозола (р = 0,0004), а также частоту объективного ответа (ЧОО) и клинической пользы (включает длительную стабилизацию болезни); выигрыш в отношении ВБП регистрировался во всех подгруппах пациенток и не зависел от экспрессии биомаркеров, продолжительность объективных ответов увеличивалась в 2 раза (20,3 мес против 11,1 мес) [18,19]. Отмечена также тенденция к увеличению ОВ в комбинированной группе: медиана ОВ достигла 37,5 мес против 34,5 мес, ОР 0,813, р = 0,42 [20].…”
Section: роль ингибиторов циклинзависимых киназ 4 /unclassified